A mixed method study of information searching behaviour of medical trainees at Postgraduate Institute of Medicine, University of Colombo - Sritharan, T.; Pathmeswaran, A.; Kumar, R. (University of Jaffna, 2022)
The rapid development of the electronic information environment and web-based services compelled the libraries to absorb new technologies and methods for in formation storage and dissemination. In order to meet the users’ workflows and be a successful information provider, it is compulsory to evaluate users’ informa tion-seeking behaviour. The objective of this study was to examine the information need and searching behaviour of Sri Lankan postgraduate medical trainees in relation to electronic information resources. The mixed-method study was guided by Leck ie’s model for the determination of information needs and information searching behaviours. The study population consisted of 815 postgraduate MD trainees in 32 medical specialities in 2014-2015 at the Postgraduate Institute of Medicine (PGIM), University of Colombo. In the quantitative component, stratified random sampling was used to select a sample of 427 trainees. Collected data were analysed by SPSS 23. In the qualitative component, 28 MD trainees participated in four focus group discussions (FGD). The FGD was held in the English language at PGIM and ranged from 30 to 45 minutes in duration. The transcribed data were uploaded to the QDA Miner Lite qualitative software and coded. Descriptive patterns were identified, concepts were drawn, and sub-themes were developed. In total, 380 out of 427 participated in the survey, giving a response rate of 89%. Findings revealed that Postgraduate trainees have different information needs. With respect to the use of electronic resources, 148 (38.9%) respondents used the PGIM library, 133 (35.0%) used other branch libraries, and 22 (5.8%). The internet was the first choice among the information channels. HINARI /PUBMED database was highly used, and ease of access was the most prominent factor for the preference of sources. More than half (55.3%) preferred both print and electronic reading. Lack of computers, lack of training, lack of time, and log-in difficulties were significant concerns. The findings of the qualitative study highlighted the need to enhance the information literacy skills and internet searching skills of medical trainees by improving internet facilities, developing the electronic environment, resources, and services, and establishing a collaborative consortium among Health Libraries with the Ministry of Health and WHO for the development of electronic collections. The study concluded that speciality plays an important role in information searching. Information literacy skills play a vital role in information-seeking behaviour. Based on the findings and conclusion, this study recommends improving the electronic information literacy skills of the PG trainees; speciality-wise orientations and workshops on information literacy skills should be conducted; arrangements should be made to provide both print and electronic resources; regular user surveys should be conducted to evalu ate the quality of the information service and steps should be taken to enhance the facilities at PGIM so that postgraduate trainees may access the necessary electronic resources quickly.
Keywords: Information need; Information searching behaviour; Electronic resources; Medical professionals; Postgraduate medical trainees